30.4k views
0 votes
Use the chain rule calculate dw/dr , dw/ds and dw/dt

W=in(x+2y+3z) , x=r^2 + t^2 , y =s^2 - t^2 , z=r^2 + s^2

User Giuppep
by
5.6k points

1 Answer

3 votes

Answer:


(dw)/(dr) = (8\cdot r)/(4\cdot r^(2)-t^(2)+5\cdot s^(2)),
(dw)/(ds) = (10\cdot s)/(4\cdot r^(2)-t^(2)+5\cdot s^(2)),
(dw)/(dt) = -(2\cdot t)/(4\cdot r^(2)-t^(2)+5\cdot s^(2))

Explanation:

We proceed to derive each expression by rule of chain. Let be
w = \ln (x+2\cdot y + 3\cdot z),
x = r^(2)+t^(2),
y = s^(2)-t^(2) and
z = r^(2)+s^(2):


(dw)/(dr) = ((dx)/(dr)+2\cdot (dy)/(dr) +3\cdot (dz)/(dr) )/(x+2\cdot y + 3\cdot z)


(dx)/(dr) = 2\cdot r


(dy)/(dr) = 0


(dz)/(dr) = 2\cdot r


(dw)/(dr) = (8\cdot r)/((r^(2)+t^(2))+2\cdot (s^(2)-t^(2))+3\cdot (r^(2)+s^(2)))


(dw)/(dr) = (8\cdot r)/(4\cdot r^(2)-t^(2)+5\cdot s^(2)) (1)


(dw)/(ds) = ((dx)/(ds)+2\cdot (dy)/(ds) +3\cdot (dz)/(ds) )/(x+2\cdot y + 3\cdot z)


(dx)/(ds) = 0


(dy)/(ds) = 2\cdot s


(dz)/(ds) = 2\cdot s


(dw)/(ds) = (10\cdot s)/((r^(2)+t^(2))+2\cdot (s^(2)-t^(2))+3\cdot (r^(2)+s^(2)))


(dw)/(ds) = (10\cdot s)/(4\cdot r^(2)-t^(2)+5\cdot s^(2)) (2)


(dw)/(dt) = ((dx)/(dt)+2\cdot (dy)/(dt) +3\cdot (dz)/(dt) )/(x+2\cdot y + 3\cdot z)


(dx)/(dt) = 2\cdot t


(dy)/(dt) = -2\cdot t


(dz)/(dt) = 0


(dw)/(dt) = -(2\cdot t)/((r^(2)+t^(2))+2\cdot (s^(2)-t^(2))+3\cdot (r^(2)+s^(2)))


(dw)/(dt) = -(2\cdot t)/(4\cdot r^(2)-t^(2)+5\cdot s^(2)) (3)

User Rjowens
by
5.0k points